Teaching ESP to Beginner Students: An Analysis of Teaching Practices Suggested in the Literature and Their Perceived Effect on Learning - Cubillo Montoya, Denis Alonso (2022)
Globalization has made job markets extremely competitive, and the revolution in information technology has made real-time communication between people in different parts of the world easy and accessible. In this context, English has reached the position of a lingua franca, and demand for specialized courses to train employees to carry out specific, job-related tasks in English, English for Specific Purposes (ESP), has increased. One important issue to consider is the fact that many workers who may be very valuable for their companies could be low-proficient in English and may struggle to reap the benefits of a demanding ESP course. The present study bears the objective of analyzing the perceived effects of teaching practices found in the literature on a group of beginner students to help them take advantage of an ESP course designed for Costa Rican municipal workers. This report includes the needs analysis carried out to pinpoint the needs, wants, and lacks of the population, the syllabus designed for the ESP course, the review of the literature consulted for the design of the course, the rationale behind the inclusion of some of those practices in said design, and a reflection about their effects on the beginner students.